2002
DOI: 10.1111/j.1654-1103.2002.tb02066.x
|View full text |Cite
|
Sign up to set email alerts
|

Trends in savanna structure and composition along an aridity gradient in the Kalahari

Abstract: Abstract. The Kalahari sand sheet occupies 2.5 million ha in southern Africa. It is an area with relatively similar deep aeolian soils, and a strong south to north gradient in rainfall, from 200 to 1000 mm mean annual precipitation (MAP) in the region studied. This provides an excellent basis for gradient studies at the subcontinental scale. This paper briefly reviews the literature on the vegetation of the Kalahari and describes the vegetation structure and composition at 11 new sites. There is a clear gradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
133
2
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(146 citation statements)
references
References 28 publications
9
133
2
2
Order By: Relevance
“…The KT is one of a set of IGBP (International Geosphere-Biosphere Programme) "megatransects" identified for global change studies (e.g., Koch et al 1995;Scholes et al 2002). Owing to its relatively uniform, deep sandy soils (Wang et al 2007), the KT provides an ideal setting to investigate changes in ecosystem structure and function (including C or nutrient cycling) along a spatial precipitation gradient while minimizing the confounding effects of soil heterogeneity (Shugart et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The KT is one of a set of IGBP (International Geosphere-Biosphere Programme) "megatransects" identified for global change studies (e.g., Koch et al 1995;Scholes et al 2002). Owing to its relatively uniform, deep sandy soils (Wang et al 2007), the KT provides an ideal setting to investigate changes in ecosystem structure and function (including C or nutrient cycling) along a spatial precipitation gradient while minimizing the confounding effects of soil heterogeneity (Shugart et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The KT is one of a set of IGBP (International Geosphere-Biosphere Programme) "megatransects" (Koch et al 1995;Scholes et al 2002) identified for global change studies. The KT traverses a dramatic aridity gradient on relatively homogenous soils (deep Kalahari sands), offering an ideal setting to study nutrient and vegetation dynamics without confounding soil effects (Wang et al 2007a).…”
Section: Introductionmentioning
confidence: 99%
“…Such knowledge, is however required in order to expand the understanding of ecosystem processes (Hahn, 1996), to relate vegetation maps to ecological properties (Devineau, 2001), and as a basis for modelling approaches (Brown & Gaston, 1996;FAO, 2001). Furthermore, the dearth of data quantifying tree physiognomies restricts our understanding of the regional and global impacts of ecological changes in savannas (Scholes et al, 2002). In this context the research question is stated thus: Which floristic composition and vegetation structure occur in different vegetation types found in the study area?…”
Section: Introductionmentioning
confidence: 99%